MULTIDRUG RESISTANT ACINETOBACTER INFECTION AND THEIR ANTIMICROBIAL SUSCEPTIBILITY PATTERN IN A NIGERIAN TERTIARY HOSPITAL ICU. - Nwadike, Victor Ugochukwu; Ojide, Chiedozie Kingsley; Kalu, Eziyi Iche (African Journal of Infectious Diseases (AJID), 2013)
Background: Acinetobacter baumannii, a non-glucose fermenting Gram negative bacillus, has emerged in the last three decades as a major etiological agent of hospital-associated infections giving rise to significant morbidity and mortality particularly in immunocompromised patients. Multidrug resistant A. baumannii (MDR-AB) is fast becoming a global threat, having developed resistance to major classes of antibiotics and carbapenem-resistant isolates have increasingly been reported worldwide as a cause of nosocomial outbreaks. Despite intensive efforts, nosocomial acquisition of MDR-AB is still a problem due to the organism’s great ability to colonize human and environmental reservoirs. This study was aimed to determine the prevalence of (MDR) AB and their antibiotic susceptibility pattern. Materials and Methods: A total of 400 specimens which include tracheal aspirates, catheter specimens of urine, wound biopsies and blood culture collected from 100 patients admitted at the Intensive Care Unit of our hospital over a period of nine months were processed following standard microbiologic procedure. Results: A total of 155 non-lactose fermenters were isolated out of which 14 (9.0%) were Acinetobacter spp. Eleven (79.0%) out of the 14 Acinetobacter spp were A. Baumanii, while 2 (14.0%) were A.lwoffi and 1(7.0%) A.calcoaceticus. All the isolates were resistant to Amoxicillin-clavulanate, Ceftriaxone, Ciprofloxacin, Ofloxacin, gentamicin and Ampicillin-sulbactam; while susceptibility to Meropenem, Amikacin and Levofloxacin were 64.3%, 50.0% and 35.7% respectively. Conclusion: The high rate of antibiotic resistance shown by Acintobacter isolates in this study demonstrates the need for antibiotic stewardship protocols to be set up in health facilities to prevent outbreaks of multi-resistant bacterial infections.